A “priesthood of knowledge”: the international thought of Henri de Saint-Simon - Eijking, J (Oxford University Press, 2021)
The French political theorist Henri de Saint-Simon is largely absent from historical International Relations (IR). This article shows why this is unwarranted and introduces him as an international thinker who made lasting contributions to IR's modern conceptual imagination. Largely responding to the French Revolution Saint-Simon rethought the parameters of international order, imagining the international as a realm separable from national politics and conformable to human agency. International order, on his account, could be actively created. This could take the shape of legislation, trade, or large-scale engineering projects: of new methods of governance. Based on a close reading of texts rarely brought into IR’s focus, this article introduces Saint-Simon as a thinker who cut across traditional IR divides and developed a central actor category of international order: impartial, knowledge-based agents of change. His understanding of international reform not only made it possible to theorize and experiment with a role in global governance for technical experts but also masked the imperial underpinnings of the international projects these experts facilitated. The article makes the case that Saint-Simon deserves a firm place in historical IR, that his thought presents an opportunity for revisiting widely held assumptions about international authority, and that a discernible Saint-Simonian strand of international thought puts typically liberal histories of global governance in question.